2014
DOI: 10.4161/epi.28078
|View full text |Cite
|
Sign up to set email alerts
|

A global profile of gene promoter methylation in treatment-naïve urothelial cancer

Abstract: The epigenetic alteration of aberrant hypermethylation in the promoter CpG island of a gene is associated with repression of transcription. In neoplastic cells, aberrant hypermethylation is well described as a mechanism of allele inactivation of particular genes with a tumor suppressor function. To investigate the role of aberrant hypermethylation in the biology and progression of urothelial cancer, we examined 101 urothelial (transitional cell) carcinomas (UC), broadly representative of the disease at present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…However, and despite the absence of genes as being exclusively associated with either high-or low-intermediate-grade tumors, the frequency and mean levels of gene-promoter methylation in the high-grade tumors were significantly higher than in the low-intermediate-grade tumors. Indeed, similar observations with respect to differences in the frequencies of methylation between high-and low-grade bladder tumors were first suggested by Ibragimova et al 47 Similar subtype and/or grade-associated differences have been reported in other tumor types including, pituitary, breast, and colon cancer subtypes. 37,48,49 In our analysis of NMIBC it remains unclear whether the increase in frequency and/or mean levels of methylation in the more aggressive tumors represents a more rapid accumulation of epigenetic changes during tumor progression, or reflects distinct epigenetic pathways of tumor development and outgrowth.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, and despite the absence of genes as being exclusively associated with either high-or low-intermediate-grade tumors, the frequency and mean levels of gene-promoter methylation in the high-grade tumors were significantly higher than in the low-intermediate-grade tumors. Indeed, similar observations with respect to differences in the frequencies of methylation between high-and low-grade bladder tumors were first suggested by Ibragimova et al 47 Similar subtype and/or grade-associated differences have been reported in other tumor types including, pituitary, breast, and colon cancer subtypes. 37,48,49 In our analysis of NMIBC it remains unclear whether the increase in frequency and/or mean levels of methylation in the more aggressive tumors represents a more rapid accumulation of epigenetic changes during tumor progression, or reflects distinct epigenetic pathways of tumor development and outgrowth.…”
Section: Discussionsupporting
confidence: 63%
“…In these cases, we identified significant over-representation of genes in processes and pathways previously reported by other groups as subject to epigenetically mediated dysregulation in tumor development. For example, these included transcription and cell signaling and adhesion, [45][46][47] suggesting possible similar roles in high-grade bladder tumors, and their validity as targets for further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This SNP has been positively associated with the expression of SETBP1, coding for an important cancer gene located on chromosome 18 that is observed also as a predominant hotspot in figure 3 c. Somatic mutations in SETBP1 [44] , as well as its expression patterns [45] , are related with myeloid leukaemia disease. Moreover in figure 3 b, we observed a very predominant hotspot regarding three CpGs belonging to three different genes but all closely located on chromosome 6; Two of them (cg02622316 located on gene ZNF96 and cg02599464 located on gene HIST1H41 ) have already been published as hypermethylated in individuals with muscle-invasive bladder cancer [46] . The first one is positively associated with many SNPs and gene expression probes, and the second is positively and negatively associated with some SNPs and only positively with some gene expression probes.…”
Section: Integrative Analysismentioning
confidence: 88%
“…Studies have shown that methylation status plays an important role in carcinogenesis in various organs, including NMIBC (ref. [21][22][23][24][25][26][27][28][29][30] ). Methylation status is a potent indicator for distinguishing patients responding to BCG from those who are failing to do so and who need the radical therapy approach 31,32 .…”
Section: Discussionmentioning
confidence: 99%